Etnomatemática na educação escolar indígena : a mobilização entre saberes ancestrais e saberes acadêmicos para o ensino da matemática na educação profissional tecnológica para a etnia Satere Mawe - Saraiva, Darlane Cristina Maciel (2022)
In order to analyze the teaching and learning processes of Mathematics, in the relationship between ancestral and academic knowledge, offered for the Integrated Technical course EJA/PROEJA/Indigenous in Agroecology, for the Satere Mawe Ethnicity, this research was carried out with students from the Technical Course in Agroecology at the Federal Institute of Amazonas, Campus Maués and other members of the academic community around this offer, who are residents in eight communities: Nova Esperança, Ilha Michilles, Vale do Quiinha, São Pedro, Nova Jerusalem, Monte Orebe, Vila da Paz and São José, all of them were from Satere Mawe ethnic group, in the Andirá-Marau Indigenous Land, totaling 35 students aged between 17 and 56 years. As for the Epistemological assumptions, we indicate dialectical materialism, as we understand that it allows, from its principles, the social phenomena interpretation, providing critical reflection between them and, for considering history as an important factor, in its intercession with the historical-social dialectic. In the field of Education, corroborating the ideas of Boaventura de Sousa Santos (2007), we dialogue with his ideas based on the Epistemology of the South and Ecology of Knowledge, aiming at the re-encounter of Science with other invisible knowledge, covered by Eurocentrist thinking, in a pedagogy of absences. The complementarity given to the theoretical contribution in this research has been following the prism of Ethnomathematics (D'AMBROSIO, 2013; MATTOS, 2020), as it is understood that it is present in all stages of the species evolution and in all cultures, giving contours to its teaching and specific strategies, specific to the perceptual field of the subjects involved in the training process. At the interface between theories of learning and the teaching of Mathematics, the theory of Meaningful Learning (AUSUBEL, 1968) was considered, especially for bringing the importance of previous knowledge to the anchoring of new knowledge and, in the context of Indigenous School Education, it envisions if the possibility of overcoming learning dissociated from the student's culture, the fragmentation of knowledge and the invisibility of these subjects in pedagogical practices in a decolonial process from Walsh (2017). The thesis that we enunciate in this research is: “The teaching of Mathematics, in Indigenous School Education, provides a space for dialogue when it values the interrelation between ancestral knowledge of each ethnic group and academic knowledge”. Therefore, this writing followed the guidelines of Qualitative Research and the methodological design of the Participant Research. The observation of this offer points us to methodological possibilities for the teaching of Mathematics in different spaces of the formal school, in this case an indigenous community, however, it worries us how such teaching practices can come dissociated from cultural knowledge already mobilized in these spaces. Talking about Indigenous School Education, especially associated with Technological Professional Education, showed how the coloniality of knowledge, being and power are present in the integration of these modalities, however, in the analysis of the object of study of this research through the dimensions of Ethnomathematics, it is possible to establish actions that break such colonial processes into transcendent and nonexcluding actions. It is not about denying academic knowledge, but walking on the fine line that intersects the dialogues between ancestral knowledge and academic knowledge.